1993
DOI: 10.1136/bmj.307.6908.846
|View full text |Cite
|
Sign up to set email alerts
|

Primary non-compliance with prescribed medication in primary care.

Abstract: Objective-To determine the rate of patients not redeeming their prescriptions (primary noncompliance) and assess the factors influencing this.Design Main outcome measures-The rate of nonredemption ofprescriptions.Results-Seven hundred and two patients (14X5%) did not redeem 1072 (5X20/) prescriptions during the study period, amounting to 11X5% of men and 16X3% of women. Non-redemption was highest in women aged [16][17][18][19][20][21][22][23][24][25][26][27][28][29] (27.6% of women) and men aged [40][41][42][4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
196
2
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(209 citation statements)
references
References 4 publications
5
196
2
6
Order By: Relevance
“…We don't have any data on the extent to which purchased drugs were actually taken. However, our data are based on dispensed drugs rather than prescribed which at least rules out primary non-compliance [35]. Finally our reference drug group may not be ideal as NSAIDs can be used either with or without a prescription, and we lack information on non-prescription use.…”
Section: Discussionmentioning
confidence: 99%
“…We don't have any data on the extent to which purchased drugs were actually taken. However, our data are based on dispensed drugs rather than prescribed which at least rules out primary non-compliance [35]. Finally our reference drug group may not be ideal as NSAIDs can be used either with or without a prescription, and we lack information on non-prescription use.…”
Section: Discussionmentioning
confidence: 99%
“…The method focuses on what the patient is currently using, either daily or as needed, and not necessarily on what the doctor has prescribed. It has been reported that specific patient groups do not redeem as many as 27% of prescriptions [30], thus a doctor may have prescribed a guideline-based regime that a patient has chosen not to have dispensed. This indicates that from a GP9s perspective this study may underestimate the proportion of patients being prescribed medication according to the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…We used data on medication retrieved from the pharmacy rather than medications prescribed by physicians, thus avoiding primary noncompliance [24].…”
Section: Discussionmentioning
confidence: 99%